Hybrid Diffuse and Sharp Interface Immersed Boundary Methods for Particulate Flows in the Presence of Complex Boundaries (Communications in Computational Physics, 2022)
A coupling framework that leverages the advantages of the diffuse andsharp interface immersed boundary (IB) methods is presented for handling the interaction among particles and particles with the static complex geometries of the environment. In the proposed coupling approach, the curvilinear IB method is employedto represent the static complex geometries, a variant of the direct forcing IB methodis proposed for simulating particles, and the discrete element method is employed forparticle-particle and particle-wall collisions. The proposed approach is validated usingseveral classical benchmark problems, which include flow around a sphere, sedimentation of a sphere, collision of two sedimenting spheres, and collision between a particle and a flat wall, with the present predictions showing an overall good agreementwith the results reported in the literature. The capability of the proposed framework isfurther demonstrated by simulating the interaction between multiple particles and awall-mounted cylinder, and the particle-laden turbulent flow over periodic hills. Theproposed method provides an efficient way to simulate particle-laden turbulent flowsin environments with complex boundaries.